"Bargaining with the status quo": Reinforcing and expanding femininities in the #bodypositive movement. Issue 1 (2nd January 2023) - Streeter, Rayanne
ABSTRACT: Contemporary representations of beauty in the United States emphasize a feminine ideal that is white, thin, able-bodied, cisgender, heterosexual, and young. However, with the advent of hashtag feminism, body positive influencers have sought to challenge the idealization of thin bodies and encourage people to rethink the boundaries of ideal femininity by positing an alternative esthetic that celebrates bodies in varying shapes and sizes. Drawing on interviews with 12 body positive influencers and an examination of 159 Instagram posts, the author examines how body positive influencers modify stereotypical understandings of femininity. The results suggest that challenging femininity and beauty in the body positive movement requires negotiation. While body positive influencers seek to expand the boundaries of femininity to include fat bodies, they also reinforce some traditional norms of femininity. However, interviews with influencers suggest that Instagram images read as reinforcing patriarchal femininity are misinterpreted queer femme imagery. By conducting both a content analysis of Instagram posts and interviews, this research captures a more nuanced understanding of the body positive movement—one that not only enforces patriarchal femininity, but also redefines femininity through fat femme representation.